Effect analysis of residual magnetism availability level on the success of voltage generation processes in self-excited induction generators - Refdinal Nazir; Syafii Syafii; Andi Pawawoi; Fajril Akbar; Yudi Arfan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
The voltage generation process is a very crucial initial stage for the successful operation of the self-excited induction generator (SEIG). The availability of residual magnetism and the adequacy of excitation capacitor value are factors that determine the success of the voltage generation process on the SEIG. This paper analyzes the effect of the availability of residual magnetism on the rotor's magnetic core. With a simple approach, the terminal voltage on the SEIG can be solved through the intersection between the magnetization curve (Xm) and the excitation curve (Xce). The shape and equation of the magnetization curve will be affected by the availability of residual magnetism. The change in residual magnetism availability will cause a change in the intersection point between the magnetization curve (Xm) and the excitation curve (Xce), which will determine the value of voltage generated by the generator. In this study, Newton Rhapson's method with numerical iteration approach has been used to analyze the effect of changes in the availability of residual magnetism on the success of voltage generation on the SEIG. The analysis results have been shown that the availability of residual magnetism with residual voltage values below 1.04 Volt will cause the failure of the SEIG to generate the terminal voltage at its nominal value. Meanwhile, the availability of residual magnetism in SEIG with residual voltage values above 1.04 Volt, will succeed in generating terminal voltage at its nominal value. For SEIG used as the object of this study, the value of Eres = 1.04 Volt is a critical value of the availability of residual magnetism.